The identification of gait asymmetry in children with juvenile idiopathic arthritis - Mpaka, Lindiwe (Department of Human Biology, 2025)
Background: Gait abnormalities are common in children with JIA, and early detection is crucial to reduce walking disability, which is a significant aspect of daily life. Analyzing gait in this population provides vital information about joint issues and walking patterns, guiding treatment goals. Addressing gait asymmetry can enhance a child's functional abilities, participation in activities, and overall quality of life. Purpose: To determine the incidence of gait asymmetry in children with JIA and to further determine the association between gait asymmetry and disease severity and functional capacity Study design: Cross-sectional Observational study. Methods: A total number of 14 children between 6-16 years of age (accompanied by their parents) that are diagnosed with JIA, were recruited. They were recruited between April and October 2023 at Tygerberg Hospital, Bellville, Cape Town during routine medical check-ups. The 6MWT was used to assess gait-related variables using the APDM wearable Technologies® incorporated within the Mobility Lab software package. We focused on the examination of five gait parameters related to the lower limbs: 1) Gait cycle duration, 2) gait speed, 3) time in stance phase, 4) stride length, and 5) time in swing phase. The test was administered in a 25 meters walkway, which was measured using a tape measurer, two cones were placed on each end, one at the beginning and one cone at the end of the distance. Results: We found a statistically significant difference in gait speed and stride length (p=0.031 and p=0.046, respectively) for the total group, considering left and right leg. Gait asymmetry was found in 8 of 14 participants when the effect size was calculated. No significant differences were found when comparing four of the gait variables between the asymmetry and no asymmetry groups. However, a statistically significant difference was observed in stride length (p = 0.04 left and p = 0.03 right) in the asymmetry and no asymmetry group. There was no statistical significance between the disease activity and the asymmetry group (p = 0.627). No statistically significant difference was observed in the total distance achieved in both the asymmetry and no asymmetry group on the 6MWT. Conclusion: Our study underscores the significant impact of gait speed and stride length on gait asymmetry in children with JIA. These gait parameters exhibited the greatest discrepancies among participants, with stride length closely associated with gait asymmetry and gait speed significantly correlated with the total distance achieved during the 6MWT. These findings suggest that both stride length and gait speed are critical factors in understanding gait asymmetry and the functional limitations experienced by children with JIA.